CHAT: Clustered hierarchical key management for wireless sensor networks using network topology. (November 2017) - Tsitsipis, Dimitris; Tzes, Anthony; Koubias, Stavros
For wireless sensor networks, key management is a challenging issue because of the limited node resources, network size, and diverse requirements, depending on the exact application. This work presents CHAT, a key management scheme based on the well-known logical key hierarchy class of protocols. CHAT exploits topological network information to reduce rekeying costs and tessellates the network into topological clusters, to further localize rekeyings, leading to greater rekeying cost reductions. A modification that adds a network key is also presented, aiming to provide a group communication scheme which still incurs a low rekeying cost.